Patient safety: knowledge, influence and attitude among physicians: an exploratory study - Noha Asem; Hend Aly Sabry; Eman Elfar (SpringerOpen, 2019)
Abstract Background Patient safety is regarded as a global problem by which both developed and developing worlds are affected. It is defined as avoidance and prevention of patient injuries or adverse events, which could result during health care delivery. This study aimed to identify physicians' knowledge, influence, and attitude toward patient's safety in the faculty of medicine, Cairo university. Materials and methods A cross-sectional study was conducted on 187 postgraduate physicians of different specialties working in the faculty of medicine, Cairo University. Anonymous self-administered questionnaires were distributed. The questionnaire is one of a series of tools designed for evaluation of the pilot implementation of the World Health Organization patient safety curriculum for medical schools. Results Calculated attitude score was relatively higher than influence, then knowledge score (median scores were 4.25, 3.1, and 2.5 respectively). There was no difference in knowledge, attitude, and influence scores by different personal characteristics as gender, specialty, workplace, graduation year except for higher influence score among physician who received inpatient safety training (p = 0.016). There was a weak positive significant correlation between knowledge and influence scores and between influence and attitude scores (r = 0.25, p = 0.002; r = 0.27, p < 0.001 respectively). Conclusion Higher patient safety positive attitude than influence and knowledge is pinpointed in physicians of different specialties in the faculty of medicine, Cairo University. This raises the attention to the importance of implementation of continuing patient safety education programs.